The Development and Implementation of a Faculty Development Residency Within Physical Therapist Education. Issue 2 (June 2019) - Salamh, Paul; Roll, Marcus; Figuers, Carol; Covington, Kyle
Abstract : Background: Over the past decade, there has been a significant proliferation of physical therapist (PT) programs within the United States. Along with these more accredited PT programs come vacant faculty positions and the need for well qualified candidates to fill core faculty rolls. The Faculty Residency Ad Hoc Group (FRAHG) of the American Board of Physical Therapy Residency and Fellowship Education was established to discuss the growing demand for qualified faculty within PT programs. A faculty development residency (FDR) was created based on the work of the FRAHG. Method: A 2-year full-time FDR was established at Duke University Doctor of Physical Therapy (DPT) Program. The program consists of didactic modules covering various facets of academia, teaching responsibilities, mentorship, and scholarly projects. The 2-year progressive curriculum builds on foundational knowledge and skillsets in order to move toward greater independence as a faculty member. Discussion: The FDR within the Duke DPT program has demonstrated the ability to identify and foster the knowledge and skills deemed valuable from the perspective of the residency directors, core faculty members, learners, and the residents themselves. Conclusion: Moving forward, the FDR appears to be a viable and meaningful option for the increasing demand for well-prepared core faculty within a DPT program. The model proposed has successfully led to the prior residents' ability to be competitive and successfully secure faculty positions upon completion. Abstract : Supplemental Digital Content is Available in the Text.